A description of Ucides occidentalis Ortmann, 1897 (Crustacea : Decapoda : Ocypodidae) zoea I. Issue 21 (11th June 2019) - Schuiteman, Michelle; Pozo-Cajas, Mireya; Dominguez-Granda, Luis; Marin Jarrin, Jose
ABSTRACT: In order to facilitate the ecological study of the economically important red mangrove crab Ucides occidentalis, we describe the zoea I phase using samples hatched from gravid females taken from the Guayas River Estuary of Ecuador. No other phases of this species' larval development have been described. The morphological differences between this developmental phase in U. occidentalis and its single congener U. cordatus that may be diagnostic include the number of segments in the pleon, the setation pattern of the basial endopodite of the maxillule, and, in maxillipeds I and II, the segmentation of the terminal plumose natatory setae.